PENGARUH MOTIVASI KERJA, KOMPETENSI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada Yayasan Tridarma Kosgoro Kabupaten Dompu) - Miftahul Su’adah; Endar Pituringsih; Ginta Ginting (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this research is: (a) to analyze the influence of motivation , competence, and compensation influential simultaneously of the performance of employees at the foundation of Tri Dharma Kosgoro, (b) to analyze the influence of motivation, competence, and compensation influential in partial of the performance of employees at the foundation of Tri Dharma Kosgoro. The populationof this research is all employees/employees foundation of Tri Dharma Kosgoro located in Dompu district about the 64, where the sample with the census research, so the entire population as many as 64 the respondents has been used in this research. Statistical analysis technique inferential used is a technique regression analysis worship of idols good by test F and test t. the result of this research showed: (a) motivation influential significantly to employee performance at the foundation is Tri Dharma Kosgoro Dompu district, (b) competence has no significant impact on employee performance at the foundation is Tri Dharma Kosgoro Dompu district, (c) compensation influential significantly to employee performance at the foundation is Tri Dharma Kosgoro Dompu District.